The characteristics of the design of human portraits embroidered on a shamanic Orgoi headwear (Mongolian Journal of Arts and Culture, 2024)
The terminology and interpretation of the unique clothing and artifacts created for specific rituals among shamanistic communities significantly due to various factors, including the spiritual beliefs and lifestyle of the ethnic groups. An essential part of this shamanistic clothing culture is the headwear, particularly the “Orgoi” hat, which features an open crown. The body of this hat is traditionally adorned with symbolic imagery crafted using conventional methods and design principles, resulting in a distinct aesthetic appearance. Aims of this study elucidate the terminology, design patterns, crafting techniques, and distinctive features of human imagery in shamanic headgear, as well as the associated traditions, composition, color, and appropriate relationships between forms and symbols.Бөөгийн оргой малгайд урласан хүний хөрөг дүрийн зохиомжийн онцлогХураангуй: Бөө мөргөлтэй ард түмний дунд түгэн дэлгэрсэн тусгай зан үйлд зориулсан өвөрмөц хувцас, эд хэрэглэл урлах соёл уламжлалын нэршил, утга тайлал нь тухайн овог угсаатны шүтлэг, амьдралын хэв маяг зэрэг олон хүчин зүйлээс хамаарч харилцан адилгүй өөр өөр онцлогтой байдаг. Бөөгийн хувцасны соёлын салшгүй хэсэг бол малгай өмсгөл бөгөөд задгай оройтой оргой хэмээх малгайн их бие дээр утга бэлгэдэл агуулсан зураг дүрсүүдийг урлахуйн уламжлалт арга, зохиомжийн дэг зурлагыг баримтлан өвөрмөц өнгө төрхтэй урлаж иржээ. Уг судалгаанд оргой малгайн нэршил болоод хэв загвар, урлах арга барил, хүний хөрөг дүрийн онцлог, уламжлалыг тодруулах, зохиомж, өнгө, дүрсийн зохист харьцааны талаар өгүүлэхийг зорилоо.Түлхүүр үгс: онгод, язгуур дүрс, тэгш хэм, самалга, орон зай